Ion exchange chromatography as a simple and scalable method to isolate biologically active small extracellular vesicles from conditioned media - Malvicini, Ricardo (2023)
In the last few years, extracellular vesicles (EVs) have become of great interest due to their potential as biomarkers, drug delivery systems, and, in particular, therapeutic agents. However, there is no consensus on which is the best way to isolate these EVs. The choice of the isolation method depends on the starting material (i.e., conditioned culture media, urine, serum, etc.) and their downstream applications. Even though there are numerous methods to isolate EVs, few are compatible with clinical applications as they are not scalable. In the present work, we set up a protocol to isolate EVs from conditioned media by ion exchange chromatography, a simple, fast, and scalable method, suitable for clinical production. We performed the isolation using an anion exchange resin (Q sepharose) and eluted the EVs using 500 mM NaCl. We characterized the elution profile by measuring protein and lipid concentration, and CD63 by ELISA. Moreover, we immunophenotyped all the eluted fractions, assessed the presence of TSG101, calnexin, and cytochrome C by western blot, analyzed nanoparticle size and distribution by tRPS, and morphology by TEM. Finally, we evaluated the immunomodulatory activity in vitro. We found that most EVs are eluted and concentrated in a single peak fraction, with a mean particle size of <150nm and expression of CD9, CD63, CD81, and TSG101 markers. Moreover, sEVs in fraction 4 exerted an anti-inflammatory activity on LPS-stimulated macrophages. In summary, we set up a chromatographic, scalable, and clinically compatible method to isolate and concentrate small EVs from conditioned media, which preserves the EVs biological activity.